Nanosystems, Drug Molecule Functionalization and Intranasal Delivery: An Update on the Most Promising Strategies for Increasing the Therapeutic Efficacy of Antidepressant and Anxiolytic Drugs - Antunes, Jéssica (2023)
Depression and anxiety are high incidence and debilitating psychiatric disorders, usually treated by antidepressant or anxiolytic drug administration, respectively. Nevertheless, treatment is usually given through the oral route, but the low permeability of the blood-brain barrier reduces the amount of drug that will be able to reach it, thus consequently reducing the therapeutic efficacy. Which is why it is imperative to find new solutions to make these treatments more effective, safer, and faster. To overcome this obstacle, three main strategies have been used to improve brain drug targeting: the intranasal route of administration, which allows the drug to be directly transported to the brain by neuronal pathways, bypassing the blood-brain barrier and avoiding the hepatic and gastrointestinal metabolism; the use of nanosystems for drug encapsulation, including polymeric and lipidic nanoparticles, nanometric emulsions, and nanogels; and drug molecule functionalization by ligand attachment, such as peptides and polymers. Pharmacokinetic and pharmacodynamic in vivo studies' results have shown that intranasal administration can be more efficient in brain targeting than other administration routes, and that the use of nanoformulations and drug functionalization can be quite advantageous in increasing brain-drug bioavailability. These strategies could be the key to future improved therapies for depressive and anxiety disorders.